Inoculation strategies affect the physicochemical properties and flavor of Zhenjiang aromatic vinegar - Ye, Xiaoting; Yu, Yongjian; Liu, Jiaxin; Zhu, Yuanyuan; Yu, Zhen; Liu, Peng; Wang, Yuqin; Wang, Ke (Frontiers in Microbiology, 2023)
Inoculation strategy is a significant determinant of the flavor quality of Zhenjiang aromatic vinegar. Herein, the comparative analyses of the effects of various inoculation strategies on the physicochemical properties, microbial community structure, and flavoring characteristics of Zhenjiang aromatic vinegar were performed. The results showed that the contents of total acid (6.91g/100g), organic acid (2099.63±4.13 mg/100g) and amino acid (3666.18±14.40mg/100g) in the direct inoculation strategy were higher than those in the traditional inoculation strategy (6.21±0.02g/100g, 1939.66±4.16 mg/100g and 3301.46±13.41mg/100g). At the same time, it can effectively promote the production of acetoin. The diversity of strains under the traditional inoculation strategy was higher than that under the direct inoculation strategy, and the relative abundance of major microbial genera in the fermentation process was lower than that under the direct inoculation strategy. In addition, for two different inoculation strategies, pH was proved to be an important environmental factor affecting the microbial community structure during acetic acid fermentation. The correlation between main microbial species, organic acids, non-volatile acids, and volatile flavor compounds is more consistent. Therefore, this study may help to develop direct injection composite microbial inoculants to replace traditional starter cultures in future research.